The African market research industry : finding new market spaces - Abdoulaye, Mohamed Cisse (2017)
The following thesis elaborates on various issues in strategy: launch strategy (especially, market selection), and strategic positioning. This paper does so through a case study based on a new venture willing to establish itself in the market: Thot Insights. This start-up would strive to provide market research services to businesses operating in Africa. It would leverage on SMS technology to collect, store, process, and deliver consumer insights. The main goal of the case is to provide readers with the unique opportunity to develop an effective business strategy for a newly created company. At the same time, raise awareness about the challenges of decision making (with imperfect information) in emerging countries. The following case study does not intend to do the following: cover all 54 markets on the continent, yet it focuses on few markets deemed strategic. Then, this paper will not provide extensive details on the company’s business plan (such as the business model, financials, or the underlying collection method). Also, it does not plan to analyze competitors in each local market, but it will adopt a broader approach, that is to say, highlight the main competitors with an extensive geographical footprint Literature related to strategic positioning, blue ocean strategy, competition mapping, and indexing, was key in analyzing the strategic issues. This lead to the following set of recommendations: launch first into Nigeria, then, expand into Ghana. The second recommendation would be to start with a traditional offering, then, educate buyers about a new set of services.